The psychological effects of reporting extreme violence: a study of Kenyan journalists. (22nd September 2015) - Feinstein, Anthony; Wanga, Justus; Owen, John
Objective: To assess the psychological health of journalists in Kenya who have reported on, and been exposed to, extreme violence. Design: Descriptive. Psychological responses were elicited to two stressors, the ethnic violence surrounding the disputed 2007 general election and the Al-Shabab attack on the Westgate Mall in Nairobi. Participants: A representative sample of 90 Kenyan journalists was enrolled. Setting: Newsrooms of two national news organizations in Kenya. Main outcome measures: Symptoms of post-traumatic stress disorder (Impact of Event Scale-revised), depression (Deck Depression inventory-revised) and general psychological wellbeing (General Health Questionnaire). Results: Of the 90 journalists approached 57 (63.3%) responded. Journalists covering the election violence ( n  = 23) reported significantly more PTSD type intrusion ( p  = 0.027) and arousal ( p  = 0.024) symptoms than their colleagues ( n  = 34) who had not covered the violence. Reporting the Westgate attack was not associated with increased psychopathology. Being wounded ( n  = 11) emerged as the most robust independent predictor of emotional distress. Journalists covering the ethnic violence compared to colleagues who did not were not more likely to receive psychological counselling. Conclusions: These data, the first of their kind from an African country, replicate findings over a decade old from Western media, namely that journalists asked to cover life-threatening events may develop significant symptoms of emotional difficulties and fail to receive therapy for them. Good journalism, a pillar of civil society, depends on healthy journalists. It is hoped that these data act as a catalyst encouraging news organisations sending journalists into harm's way to look out for their psychological health in doing so.